Hypercholesterolemia due to lipoprotein-X manifesting as pseudohyponatremia in a patient with cholestasis. Issue 2 (4th March 2023) - Azad, Farhan; Mughaedh, Norah Abu; Alloghbi, Abdurahman; Tawhari, Ibrahim
Abstract: Pseudohyponatremia is an often misdiagnosed condition that needs to be managed by addressing the underlying cause. Treatment of hyponatremic patients with intravenous fluids without ruling out pseudohyponatremia may aggravate a patient's hyponatremia and result in adverse outcomes. In a patient whose sodium is deteriorating, it is critical to diagnose pseudohyponatremia early in the course and acquire necessary consultations, even if the patient is asymptomatic. We discuss a case of a man in his 20s with a history of liver transplantation who presented with unexplained dangerously low sodium while being asymptomatic. The case illustrates an uncommon cause of pseudohyponatremia due to lipoprotein-X hypercholesterolemia in a patient with cholestatic liver disease.